2010
DOI: 10.3325/cmj.2010.51.501
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Venoarterial Carbon Dioxide Gradient in Patients with Severe Sepsis and Septic Shock

Abstract: V-a Pco(2) was a significant predictor of fatal outcome only in the non-ventilated group of patients. Ventilated patients are more likely to be admitted with a less favorable clinical status, and other variables seem to have a more important role in their outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In the current study, there was no correlation between central and pulmonary CO2 gaps with cardiac output. , many studies [12,25,27] stated an increased central CO2 gap in low cardiac output states due to venous flow stasis which decreased with increased cardiac output . Cuschieri et al [25] showed the correlation between the central CO2 gap and the pulmonary CO2 gap with cardiac index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, there was no correlation between central and pulmonary CO2 gaps with cardiac output. , many studies [12,25,27] stated an increased central CO2 gap in low cardiac output states due to venous flow stasis which decreased with increased cardiac output . Cuschieri et al [25] showed the correlation between the central CO2 gap and the pulmonary CO2 gap with cardiac index.…”
Section: Discussionmentioning
confidence: 99%
“…Cuschieri et al [25] showed the correlation between the central CO2 gap and the pulmonary CO2 gap with cardiac index. Troskot et al [12] concluded in their study of patients with severe sepsis and septic shock that the central CO2 gradient could predict fatal outcomes in non-ventilated patients only. Also, Mallat et al [11] in their study on 80 patients with sepsis, measured the central CO2 gap and cardiac index using PICCO technology at time 0 (start of the study) and at time 6 (6 hours after resuscitation) and found a correlation between CO2 gap and CI at T0 (r = -0.69, P<0.0001) and at T6 (r = -0.54 P<0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies in critically ill adults after abdominal surgery or with septic shock demonstrated that patients with an increased AVCO 2 gradient were more likely to have increased postoperative complications and poor outcomes, including death - even in patients who had a normal ScVO 2 (>70%) (6, 9, 2223). In our cohort, increased AVCO 2 was associated with poor outcome even after controlling for STAT category and other covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Widening of AVCO 2 represents an imbalance between CO and tissue CO 2 production. AVCO 2 monitoring is gaining momentum as a surrogate of CO in critically ill adults; an increased AVCO 2 gradient is associated with decreased CO and morbidity in adult patients with shock from hemorrhage sepsis, and cardiac surgery (19). …”
Section: Introductionmentioning
confidence: 99%